The impact of an electronic guide on students' self‐directed learning in simulation clinic. (3rd September 2020) - Terry, Andrew; Liu, Danny; Divnic‐Resnik, Tihana
Abstract: Introduction: Simulation training on high‐fidelity simulated models have been used to provide a safe and effective training platform for dental students to develop the skills necessary to treat patients. To surpass challenges of traditional pedagogies in simulation training and reinforce self‐directed learning, a bespoke computer application, PerioPal, was designed to complement training of dental students in periodontal instrumentation. Materials and methods: This study evaluated the impact of PerioPal on a cohort of 92 second‐year dental students at an Australian University. During the first semester in 2019, they received traditional simulation periodontal instrumentation training (control semester). In the following semester, PerioPal was implemented as a technological teaching adjunct (intervention semester). Student perceptions of their learning experiences were gathered through a qualitative and quantitative questionnaire. Impact on student performance was evaluated through comparing periodontal instrumental assessment results in control and interventionsemesters. Results: With introduction of PerioPal, students perceived that the simulation clinic learning environment, better contributed to the speed at which they learnt new instrumentation as well as being able to self‐pace their work. They commented that instructional videos and independent learning were most beneficial. Interestingly, students suggested that PerioPal aided their preparation for theoretical assessments more than their practical assessments. After introduction of PerioPal a minor improvement of average practical assessment marks was observed but could not be statistically confirmed as significant. Conclusion: Although the computer‐supported learning did not lead to improvement of the students' practical performance a positive effect on the student self‐paced learning experience and engagement in simulated environment were observed.